(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to know and find the relationship and influence of the elements of marketing intelligence in the comprehensive marketing of the National Insurance Company. The independent variable was represented by the element of marketing intelligence and its dimensions, while the dependent variable was represented by comprehensive marketing and its dimensions. The problem of the study was defined by raising questions about the nature of the relationship and influence between the independent variable (elements of marketing intelligence) and the dependent variable (comprehensive marketing). The research used the questionnaire as a main tool to obtain data. The research also adopted the descriptive analytical approach, where the main and sub-variables were described, as well as analyzing the correlation and influence between the variables. The hypotheses were selected by applying statistical methods using the computer program (spss v.25), (Amos v.24). The research reached a set of results and proposals, the most important of which is the existence of a significant correlation between the study variables and their dimensions at the macro and micro levels, if the correlation coefficients are high. These results confirm the strong correlation between the variables, and the research results confirmed the existence of a significant impact of the elements of marketing intelligence in comprehensive marketing at the general level.